Clinical comparison of transfemoral vs. distal transradial access for lower extremity arteriography - Feng, Zibo; Zeng, Qionglin; Zhu, Youpeng; Wang, Ting-yu (Frontiers in Surgery, 2026)
ObjectivesThis study aims to evaluate the feasibility and advantages of the distal transradial approach (dTRA) for assessing blood supply in patients with lower limb ulcers.MethodsThis study analyzed 66 patients with chronic lower limb ulcers who underwent lower limb angiography between December 2023 and October 2024. Among them, 44 patients were in the transfemoral access (TFA) group, and 22 patients were in the dTRA group. The success rate of the procedure, contrast dosage, time consumed for contrast, postoperative complications, patient Satisfaction Score and objective analysis of image quality were recorded and statistically analysed using SPSS 22.0.ResultsThe analysis revealed that there was no statistically significant difference in the procedural success rates between the two groups, with the TFA group achieving a 95% success rate compared to 86% in the dTRA group (P = 0.41). The amount of contrast agent used was significantly higher in the dTRA group than in the TFA group (70.79 ± 13.25 mL vs. 60.10 ± 16.98 mL, P = 0.02). However, there was no statistically significant difference in the complication rate (2.3% in the TFA group vs. 0% in the dTRA group, P = 1.00). Slightly more time-consuming imaging in the dTRA group (30 min vs. 25 min, P = 0.06). Patient satisfaction score in the dTRA group (4.16 ± 0.60) was better than the TFA group (3.12 ± 0.63, p = 0.00). The CNR (13.99 ± 7.92) in the dTRA group was lower than that in the TFA group (21.31 ± 10.57) (P = 0.009).ConclusionsThe dTRA demonstrates diagnostic efficacy comparable to the TFA in evaluating lower limb blood supply in chronic lower limb ulcers patients, and significantly improves patient comfort with its minimally invasive access, early mobility, and low complication risk.